Nutraceutical Drink as Immune Booster Made from Red Ginger Combined with Lime and Honey to Prevent Viral Infection - Hasanah, Nur; Utami, Sheila Meitania; Ismaya, Nurwulan Adi; Imansari, Aulia Nadya Rizki (Jurnal Kefarmasian Indonesia, 2025)
Nutraceutical drinks are increasingly being chosen by the public as alternative medicine or as supportive therapy for disease prevention, offering minimal side effects with long-term use. This trend has gained momentum, mainly due to the rising incidence of COVID-19 and the emergence of highly transmissible variants. The combination of red ginger, lime juice, and honey will produce a healthy drink preparation containing antioxidants with vitamin C levels as an immune booster. This study aims to formulate a nutraceutical drink made from red ginger ((Zingiber officinale var. rubrum) combined with lime (Citrus aurantifolia) and honey also determine the antioxidant activity and the highest vitamin C levels. Physical stability tests include organoleptic, homogeneity, pH, specific gravity, viscosity, and accelerated stability tests using freeze-thaw cycling method. The antioxidant activity test using DPPH (1,1-diphenyl-2-picrylhydrazyl) method and analysis of vitamin C levels using the UV-Vis spectrophotometry method. The formulation was made with variations of lime juice FI (1%), FII (2%), and FIII (4%). The results of physical stability of the three formulations are not much different but based on organoleptic, FI has the best taste which is not too spicy and we are sure that most people will like it. Meanwhile, the highest antioxidant activity was possessed by FIII with an IC50 value of 11.21 ppm, which is classified as very strong and has the highest vitamin C content of 9103.88 µg/mL.